Articulation paths in research on medical education at San Fernando Faculty of Medicine and research on human resources in Peru - Mendoza Arana, Pedro Jesús (2014)
Introduction: Previous research has shown lack of articulation between university based research and research priorities as defined by the national health authority. Objectives: To identify explanatory factors for lack of articulation between university research activities and knowledge needs as defined by users. Design: Qualitative case study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos (UNMSM), Lima, Peru. Participants: Informants from both the university and the national health authority. Methods: The study was based in semi structured interviews to key informants, from the university and the national health authority. Main outcome measures: Lack of articulation explanatory factors. Results: Explanatory factors identified were: a) Research funding culture depending on own university limited resources, and not allowing proposed nationwide studies such as those required by the Ministry of Health (MOH); b) Low UNMSM visibility at MOH with consequent unawareness of its publications on Human Resources; c) UNMSM research visualized as basically individual efforts and not as the result of research teams and research lines. Conclusions: Research lines concordant with needs and capacities of human resources research priorities were: a) Articulation of undergraduate education and health needs; b) Use of information and communication technology (ICT) in training; and c) Impact of experiences on competencies development for graduate education and specialization.